Kontekstualisasi pemikiran S. R. Ranganathan dalam perkembangan dunia perpustakaan masa kini - Sholihah, Husna Amalina; Yumna, Atikah Nur Aini; Zulaikha, Sri Rohyanti (Pustaka Karya : Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
Science is dynamic so it continues to develop over time. A number of figures contributed to coloring scientific dynamics, one of which was S.R Ranganathan who dedicated his life to the world of libraries. His name is well known as the Father of Libraries in India and his ideas spread throughout the world. His magnum opus Prolegomena to Library Classification and Colon Classification stimulated the birth of the Dewey Decimal Classification. Apart from that, his work as outlined in the Five Laws of Library Science had a major impact on the development of the world of libraries. This research uses a qualitative research method with a type of literature study (library research), then the data that has been obtained will be followed by reading and note-taking techniques and then processed the data analytically and descriptively. This article aims to find out the contextualization of S.R Ranganathan's five laws in the development of today's library world. These five laws read: Books are for use, Every reader his or her book, Every book its reader, Save the time of readers, and The library is a growing organism are still relevant today which is synonymous with technology and digitalization.